Cretaceous - Tertiary carbonate platform evolution and the age of India – Asia collision along the Ladakh Himalaya (NW India) - Green, Owen R; Searle, Michael P; Corfield, Richard I; Corfield, Richard M (Himalayan Journal of Sciences, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–> DOI = 10.3126/hjs.v5i7.1256 Himalayan Journal of Sciences Vol.5(7) (Special Issue) 2008 p.54